Use of organic and inorganic fertilization in zero-discharge tanks and ponds and its effects on plankton and shrimp Litopenaeus vannamei performance - Héctor M. Esparza-Leal (Revista de Biología Marina y Oceanografía, 2016)
The aim of this study was to investigate the effects of organic (molasses) and inorganic (Nutrilake ® ) fertilization on plankton, water quality, and shrimp Litopenaeus vannamei performance reared in zero-discharge tanks and ponds. The findings showed that in tanks, the organic fertilization induced highest survival and production, and low total ammonia-N concentration; however, this effect was not observed in the ponds. In both tanks and ponds, the inorganic fertilization increased nitrogen levels. The phytoplankton abundance increased in both tanks/ponds with the fertilization treatments. Shrimp production in the tanks and ponds fertilized almost doubled compared with unfertilized treatments.